Meningkatkan Hasil Belajar Bahasa Indonesia Materi Kosakata Dengan Menggunakan Media Kartu Kata Pada Siswa Kelas II SDK Wegoknatar - Yohanes Frederik Pati; Lukas Bera; Maria Angelina Fransiska Mbari (Departement of Mathematics Education, 2023)
This study aimid to improve vocabulary learning outcomes by using word cards for garde II student at Wegoknatar Private Elementary School. This research was a calsroom action research (rsCAR) which was designed to assist teacher (researche) in finding and solving problems that occurred in the classroom. This CAR was carried out in two cycles involving 15 grade II students. The results indicated that after giving action for the two cycles, the vocabulary learning results increased. In the first meeting of the cycle I the score was 37,86% and in the second meeting the score was 60% meaning that not yet reached KKM. In the first meeting of cycle II there was an increase of 90% and at the second meeting, it increased to 100%. This implied that the use of word card media was able to improve vocabulary learning outcomes